Unraveling the Potential of Micro-nano Bubbles in Water Treatment: A Review Focusing on Physicochemical Properties, Generation Methods, and Environmental Impacts - Li, Ling; Liu, Honglin; Huang, Yingping; Hong, Feng; Yuan, Xi; Cai, Wei; Chen, Chuncheng; Huang, Di (The Global Environmental Engineers, 2024)
With the advancement of industrialization, water pollution has become a pressing global environmental issue. Traditional water treatment technologies are struggling to remove emerging contaminants and meet current discharge standards, against this backdrop, micro-nano bubbles (MNBs) technology has attracted considerable research attention due to its unique physicochemical properties, such as long-term stability, high internal pressure, photoelectric characteristics, and reactive oxygen species (ROS) generation capabilities, especially in its combination with advanced oxidation processes (AOPs). A comprehensive understanding of MNBs generation and utilization is significant for developing green, economical, and highly effective wastewater treatment technologies. Herein, on the basis of the comprehensive literature survey, this review article systematically studied the distinctive characteristics of MNBs, along with the methodologies employed for their generation. It concurrently explores the characterization methods used to assess the properties of MNBs, which is instrumental for subsequent analyses on how these properties can enhance the catalytic performance of AOPs. Finally, this article explores the potential applications of MNBs in the environmental sector and points out the direction for future research, including the development of more efficient and cost-effective MNBs generation technologies, in-depth exploration of their mechanisms in AOPs, and comprehensive environmental impact assessments. This review aims to provide readers with an in-depth understanding of the intrinsic correlation between the properties and applications of MNBs, thereby enabling their optimal utilization in the environmental remediation.